##### Ad

related to: U

sin(

**u**/ 2) = sqrt( (1 - cos(**u**)) / 2) cos(**u**/ 2) = sqrt( (1 + cos(**u**)) / 2) tan(**u**/ 2) = sin(**u**/2) / cos(**u**/2) = sqrt...sqrt( (8/5) / 2) = sqrt( 4/5 ) = 2 / sqrt(5) = 2 * sqrt(5) / 5 sin(**u**/2) = 2 * sqrt(5) / 5 sqrt( (1 - 3/5) / 2) = sqrt( (2/5) / 2...3 Answers · Science & Mathematics · 06/08/2010

**u**+12/**u**^2 +**u**+2/3u**u**^3 + 12 +**u**^3 +2u/3 2u^3 + 2u/3 + 12 6u^3 +2u + 363 Answers · Science & Mathematics · 26/10/2007

∫

**u**d**u**/(16 +**u**^2) Let w = 16 +**u**^2 then dw = 2**u**d**u**so (1/2) dw =**u**d**u**We now have (1/2) ∫ dw/w = (1/2) ln w = (1/2) ln (16 +**u**^2) + C3 Answers · Science & Mathematics · 09/04/2011

(

**u**+7)^2 = 2u^2 +8u +42**u**^2+14u+49=2u^2+8u+42 0=**u**^2-6u-7 0=(**u**-7)(**u**+1)**u**-7=0 or**u**+1=0**u**=7 or -17 Answers · Science & Mathematics · 02/11/2008

do

**u**have a sense of humor?what kind is dry, black, or how would**u**describe your self are**u**confident was school hard for**u**what...1 Answers · Arts & Humanities · 15/04/2010

**u**^2 x^4 -**u**^2 re-order (this isn't exactly necessary it just makes it easier) -1u^2 +**u**^2 x^4 factor out the greatest common factor/ gcf (**u**^2)**u**^2 (-1 + x...3 Answers · Science & Mathematics · 31/07/2010

**u**= 4i - 2j tan(**u**) = - 2/4 = - 1/2 → angle_**u**= - 26.565° v = i + 3j tan(v) = 3/1 = 3 → angle_v = 71.565° angle between**u**and v: = 71.565 - (- 26.565) = 71.565 + 26.565 = 98.130°3 Answers · Science & Mathematics · 25/05/2014

Given: (5u+3/4) = (

**u**-4/5) +11 ()s are not needed so we remove them: 5u + 3/4...4/5 + 11 - 3/4 Create a common denominator on the right hand side: 5u -**u**= - 16/20 + 220/20 - 15/20 Combine like terms: 4u = 189/20 ...1 Answers · Science & Mathematics · 25/08/2012

**u**can call people with skype, skype to skype is free plus**u**can put credits its really low prices but**u**must be ...2 Answers · Consumer Electronics · 08/07/2008

**u**= tan(x/2) 1/**u**= cot(x/2) (1/**u**)^2 = cot(x/2)^2 (1/**u**)^2 = csc(x/2)^2 - 1 1 + (1/**u**)^2 = csc(x/2)^2 (1 +**u**^2) /**u**^2 = csc(x/2)^2**u**^2 / (1 +**u**^2) = sin(x/2)^2**u**^2 / (1 +**u**^2...1 Answers · Science & Mathematics · 29/04/2013

##### Ad

related to: U